2012
DOI: 10.4103/0257-7941.107362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous extracts of Achyranthes aspera Linn. on experimental animal model for inflammation

Abstract: Background:Achyranthes aspera is known as Chirchita (Hindi), Apamarga (Sanskrit), Aghedi (Gujarati), Apang (Bengali), Nayurivi (Tamil), Kalalat (Malyalam) and Agadha (Marathi) in our country. It possesses valuable medicinal properties and used in treatment of cough, bronchitis and rheumatism, malarial fever, dysentery, asthma, hypertension and diabetes in Indian folklore. Present study was designed to evaluate anti-inflammatory activity of an aqueous extracts of Achyranthes aspera (AEAA).Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“… Amaranthaceae Leaves Pneumonia and asthma Antihistaminic, anti-inflammatory, mast cell stabilizer and bronchoprotective effect. Inhibits action of histamine, acetylcholine and 5-HT [ 139 , 140 ] Albizia lebbeck Benth Moraceae Bark Flu, cough, lung problems Bronchodialator, Anti-allergic, Mast cell stabilizing property due to histamine release and cytokine expression of antigen –ige activated mast cells [ 141 , 142 ] Alstonia scholaris Fabaceae Bark, Leaves Asthma Bronchodialator, anti-tussive effect against sulfur dioxide induced mice coughing and citric acid induced guinea pigs coughing. Anti-asthmatic activity against histamine induced bronchoconstriction [ 143 , 144 ] Althaea officinalis L. Lythraceae Flowers, leaves, roots, fruits Asthma and bronchitis Cough suppressant activity in citric acid-induced cough reflex [ 145 ] Artemisia vulgaris Asclepiadaceae Leaves Asthma Bronchodilator due to anticholinergic and Ca 2+ antagonist mechanisms [ 146 ] Artemisia maritime Asteraceae Aerial parts Cough Bronchodilator activities mediated possibly through dual blockade of calcium channels and phosphodiesterase [ 102 ] Adhatoda vasica Capparidaceae Whole plant Cough, bronchitis, asthma Antiallergic, anti-anaphylact...…”
Section: Resultsmentioning
confidence: 99%
“… Amaranthaceae Leaves Pneumonia and asthma Antihistaminic, anti-inflammatory, mast cell stabilizer and bronchoprotective effect. Inhibits action of histamine, acetylcholine and 5-HT [ 139 , 140 ] Albizia lebbeck Benth Moraceae Bark Flu, cough, lung problems Bronchodialator, Anti-allergic, Mast cell stabilizing property due to histamine release and cytokine expression of antigen –ige activated mast cells [ 141 , 142 ] Alstonia scholaris Fabaceae Bark, Leaves Asthma Bronchodialator, anti-tussive effect against sulfur dioxide induced mice coughing and citric acid induced guinea pigs coughing. Anti-asthmatic activity against histamine induced bronchoconstriction [ 143 , 144 ] Althaea officinalis L. Lythraceae Flowers, leaves, roots, fruits Asthma and bronchitis Cough suppressant activity in citric acid-induced cough reflex [ 145 ] Artemisia vulgaris Asclepiadaceae Leaves Asthma Bronchodilator due to anticholinergic and Ca 2+ antagonist mechanisms [ 146 ] Artemisia maritime Asteraceae Aerial parts Cough Bronchodilator activities mediated possibly through dual blockade of calcium channels and phosphodiesterase [ 102 ] Adhatoda vasica Capparidaceae Whole plant Cough, bronchitis, asthma Antiallergic, anti-anaphylact...…”
Section: Resultsmentioning
confidence: 99%
“…ere is a research telling us that oxymatrine, which is one of the effective constituents of Radix Sophorae Flavescentis, exerts cardioprotective effect by preventing ventricular remodelling, myocardial hypertrophy, and myocardial fibrosis [12]. Other studies have indicated that Herba Achyranthis Asperae not only exhibits promising anti-inflammatory activity but also shows significant gastroprotective activity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the medicinal plants currently being developed is Sangketan (Achyranthes aspera L.). The plant is reported to have several medicinal properties and is used as an emmenagogue, purgative, diuretic, antimalarial, antihyperlipidemic, estrogenic, antileprotic, antispasmodic, cardiotonic, antibacterial, and antiviral agent in various traditional systems of medicine [3][4][5][6][7]. However, the raw material (Simplicia) and the extract needed to undergo a thorough standardization process.…”
Section: Introductionmentioning
confidence: 99%